VAT gap estimation and influence of selected methods of fiiancial administration on its reduction - Lukáš Moravec; Jana Hinke; Monika Borsiczká (DANUBE: Law, Economics and Social Issues Review, 2021)
The aim of this contribution is to quantify the influence of selected methods on elimination of value added tax gap in the Czech Republic within the researched period 2015-2016. To find a possible share of influence of the VAT control statement on tax fraud following priority methods were set: VAT control statement invitation, initiatives from pairing check reports, tax checking and procedures for doubt removal. By quantifying these methods, the values of theoretical benefits are measured and further compared with value added tax gap within the researched period. To set the VAT gap estimation a method was used that calculates via cleaning gross domestic product based on the database of national accounts. By using this approach it was found out that with the influence of selected methods of financial administration there was a tax gap decrease in 2015 by 5.54% and for 2016 by 4.00%.
Keywords: 330; VAT Control Statement; VAT Gap; Tax Administration; Tax Collection; Tax Fraud